Utilizing Google Earth Data to Assess Spatial-Temporal Land Use Changes around Jatibarang Reservoir, Semarang City - Ayu Handayani; Adi Wibowo (MO.RI Publishing, 2023)
This study aims to assess the spatial-temporal land use changes around Jatibarang Reservoir in Semarang City, Indonesia City from 2012 to 2022, utilizing Google Earth data. The Jatibarang Reservoir and its surrounding areas have been subject to rapid urbanization and land use transformations in recent years, leading to significant environmental and socio-economic implications. The classification accuracy of seven land use categories was validated, demonstrating a high level of accuracy. The analysis reveals a dominance of agricultural land use, with notable shifts observed in forest cover, settlements, and reservoir areas. Population growth, economic development, and policy interventions are identified as the main drivers behind these land use changes. The spatial analysis using Nearest Neighbor Analysis (NNA) indicates a scattered distribution pattern of land use changes, primarily concentrated in the western part of the reservoir area. These land use changes have significant social, economic, and environmental implications, impacting the sustainability of the reservoir and surrounding areas. The study highlights the need for improved data quality, rigorous validation methods, and spatial modeling approaches in future research. By understanding the dynamics of land use changes and their implications, policymakers and stakeholders can make informed decisions for sustainable land management and environmental conservation in similar contexts.